Practitioners’ Experiences of School Readiness in Rural Early Childhood Centres in QwaQwa Free State, South Africa - Mahudi Mofokeng (Research and Advances in Education, 2024)
The analysis of the school preparation experiences of rural early childhood practitioners. Multiple complex issues exist regarding school preparedness in South Africa. Research has found that many South African children are unprepared for formal schooling. Some of the challenges experienced by these young learners were low reading strength, learning setbacks and complications, and sluggish general development. As a result of these issues, young children face long-term repercussions. These include the inability to escape the cycle of poverty, lack of educational support, and poor socioeconomic conditions within their environment. Therefore, it can be argued that teaching within the South African public schooling context is marred with difficulties and unforeseen challenges. It is difficult to imagine how to modify South African infrastructure so all children can reach their full potential. Given that our ancient past is still rife with historical and power changes, the government must consider several factors while developing ways to aid transformation. This study investigated the perspectives of practitioners on school preparedness. At the same time, it investigates the significant learning at the grass-roots level that emerged from participation in a critical paradigm-based participatory action research project. The study is anchored in a philosophical methodology that leverages Practitioners’ idea that early childhood learners are ready for formal school. They do not emphasize play as a pedagogy for learning in preparation for school readiness. This paper is grounded in constructivism, which helps comprehend how school readiness knowledge improves formal education for young students. The author used the qualitative research approach with an interpretive paradigm to explore practitioners’ school readiness experiences. The author developed a semi-structured interview schedule to collect data from six practitioners in the Thabo-Mofutsanyana district in the Free State Province. The findings revealed practitioners lacked appropriate training and support in preparing young learners in ECD centres. Furthermore, practitioners lacked appropriate pedagogical skills to strengthen teaching and learning. The study recommended that practitioners receive ongoing professional teacher development in school readiness and use various teaching and learning strategies such as play pedagogy.